Are factors affecting RFID adoption different between public and private organisations?. (2017) - Lee, Sangjae; Park, Yong-Jae; Rim, Myung-Hwan; Kim, Byung Gon
While radio frequency identification (RFID) technology is becoming widely used in supply chains for several public and private applications in Korea, the widespread diffusion of RFID across various industries is yet to be expected. This study suggests two objectives for RFID research: (1) To show that factors (technological, organisational, and environmental factors) affecting RFID adoption are different between public and private organisations in Korea. (2) To apply a balanced score approach (BSC) to assess the organisational performance after RFID adoption and show differences in the performance of RFID adoption between public and private organisations. Technological complexity, security, and size are the most important factors for public RFID adopters, while technological compatibility, adoption cost, and competitive pressure are the most important determinants for RFID adoption in private organisations. It turns out that RFID adoption positively influences the organisational performance in aspects of learning and growth, internal process, and customers rather than financial performance. Furthermore, the emphasis on the four measures of BSC is different between public and private organisations, as the RFID adoption by public organisations is more significantly linked to financial performance than private organisations. In contrast, private organisations are more likely to produce learning and growth, internal process efficiency, and customer performance than public organisations.